The Relationship Between Parental Attachment and Mobile Phone Dependence Among Chinese Rural Adolescents: The Role of Alexithymia and Mindfulness - Li, Xiaoqing; Hao, Chenrui (Frontiers in Psychology, 2019)
This study examined the relationship between parental attachment and mobile phone dependence (MPD) as well as the roles of alexithymia and mindfulness. We hypothesized that parental attachment would predict MPD, and alexithymia as a mediator and mindfulness as a moderator in this association. Data were collected from 3 middle schools in rural areas of Jiangxi and Hubei Province in China. A total of 693 valid questionnaires were collected (Boys = 352, Girls = 322; Mage = 14.88, SD = 1.77), and the adolescents’ parental attachment, alexithymia, mindfulness and MPD were surveyed. Among the results, parental attachment negatively predicted MPD and alexithymia were exerting partial mediation effect between parental attachment and MPD. Moreover, the moderating effect was observed. The effect of alexithymia on MPD was weakened under the condition of high level of mindfulness. These results were conducive to understand “how” and “when” the parent-child relationship affected MPD in Chinese rural adolescents from the perspective of attachment theory. And the implications for the contributions of alexithymia and mindfulness to insecurely parental attached adolescent’s MPD were also discussed.